Preparing Healthy Products Having High Nutritional Value By Using Some Food Wastes - Eman, R.M. Abbas; Eman, A.A. Eldanasory; Rania, M.M. Mansour (Food Technology Research Journal)
Agri-food industry wastes and by-products include highly valuable components that can upgraded, providing low-cost bio actives or used as an alternative healthy food source. In this context, by-products from olive and date production. This study aimed to evaluate the nutritional and sensory properties of crackers prepared using date seeds and olive stones powder. Three different substituted levels of date seeds and olive stones (10%, 20% and 30%) were used in preparing crackers. The chemical composition of them and prepared crackers were determined. Bioactive compounds in date seeds and olive stones powder were determined. Sensory properties of prepared crackers were evaluated. Results showed that the content of moisture, ash, protein, fat, fibers, flavonoids and some minerals (Fe, Ca, Na) in olive stones powder were higher than date seeds, while carbohydrates, phenols and minerals (K, Mg, Mn, Cu, Zn) content in date seeds powder were higher than olive stones powder. The study concluded that utilization of date seeds and olive stones powder improved the nutritional value of crackers.